La globalización y su influencia en la identidad cultural del Centro Poblado Kechwa el Wayku Lamas 2023 - Tuesta Vela, Lesly (2025)
The general objective of this research was to determine the level of influence of globalization on the cultural identity of the Kechwa el Wayku Population Center, Lamas 2023, for this, the quantitative methodology was applied, of non-experimental, explanatory, cross-sectional and prospective design, the sample being made up of 324 inhabitants of a population of 2054, selected by simple random sampling; for data collection, the survey was used as an instrument, the questionnaire. The results show a Spearman correlation between globalization and cultural identity with a value of 0,788, in the historical dimension of 0,991, in its linguistic dimension of 0,926, in its symbolic dimension of 0,636, in its territorial dimension of 0,598, indicating a strong and positive influence. The statistical significance p = 0,000 supports that this relationship is highly significant between globalization and each of the dimensions. Finally, the model shows that globalization directly and positively influences cultural identity, suggesting that global processes contribute to the strengthening or reconfiguration of cultural expressions in the population analyzed, accepting the hypothesis that globalization significantly influences the cultural identity of the community.